THE EFFECTIVENESS OF CONTEXTUAL TEACHING AND LEARNING MODELS IN IMPROVING STUDENT LEARNING OUTCOMES IN JUNIOR HIGH SCHOOLS - Nur Adilah; slamet Riyadi; Suwardi, Suwardi (Ikatan Dosen Menulis, 2024)
This research aims to systematically examine the effectiveness of the contextual learning model in improving Islamic Religious Education learning outcomes for junior high school (SMP) students. Apart from that, this research also wants to identify the factors that influence the success of implementing this learning model. This research uses a Systematic Literature Review approach. Data was obtained through searching for relevant literature from the Scopus data base in the 2019-2024 publication time period using keywords such as